Gradients in Water Potential and Turgor Pressure along the Translocation Pathway during Grain Filling in Normally Watered and Water-Stressed Wheat Plants - Fisher, Donald B. (American Society of Plant Physiologists, 2000)
The water relations parameters involved in assimilate flow into developing wheat (Triticum aestivum L.) grains were measured at several points from the flag leaf to the endosperm cavity in normally watered (Ψ ≈ −0.3 MPa) and water-stressed plants (Ψ ≈ −2 MPa). These included direct measurement of sieve tube turgor and several independent approaches to the measurement or calculation of water potentials in the peduncle, grain pericarp, and endosperm cavity. Sieve tube turgor measurements, osmotic concentrations, and Ψ measurements using dextran microdrops showed good internal consistency (i.e. Ψ = Ψ(s) + Ψ(p)) from 0 to −4 MPa. In normally watered plants, crease pericarp Ψ and sieve tube turgor were almost 1 MPa lower than in the peduncle. This suggests a high hydraulic resistance in the sieve tubes connecting the two. However, observations concerning exudation rates indicated a low resistance. In water-stressed plants, peduncle Ψ and crease pericarp Ψ were similar. In both treatments, there was a variable, approximately 1-MPa drop in turgor pressure between the grain sieve tubes and vascular parenchyma cells. There was little between-treatment difference in endosperm cavity sucrose or osmotic concentrations or in the crease pericarp sucrose pool size. Our results re-emphasize the importance of the sieve tube unloading step in the control of assimilate import.